2019
DOI: 10.1037/xap0000180
|View full text |Cite
|
Sign up to set email alerts
|

Caricaturing as a general method to improve poor face recognition: Evidence from low-resolution images, other-race faces, and older adults.

Abstract: There are multiple well-established situations in which humans' face recognition performance is poor, including for low-resolution images, other-race faces, and in older adult observers. Here we show that caricaturing faces-that is, exaggerating their appearance away from an average face-can provide a useful applied method for improving face recognition across all these circumstances. We employ a face-name learning task offering a number of methodological advantages (e.g., valid comparison of the size of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 64 publications
(128 reference statements)
1
15
0
Order By: Relevance
“…All these signals involve only small physical variations in faces, implying they are likely to be poorly perceived by patients with low-resolution vision, including AMD patients. Caricaturing offers hope of improving recognition of these types of subtle information given that both our present findings and our previous studies of simulated low vision (Dawel et al, 2019;Irons et al, 2014) show that caricaturing tends to be effective particularly when performance is initially impaired, at least as long as accuracy does not become so poor it hits floor.…”
Section: Caricaturing and Difficulty Of The Expression Recognition Tasksupporting
confidence: 64%
See 2 more Smart Citations
“…All these signals involve only small physical variations in faces, implying they are likely to be poorly perceived by patients with low-resolution vision, including AMD patients. Caricaturing offers hope of improving recognition of these types of subtle information given that both our present findings and our previous studies of simulated low vision (Dawel et al, 2019;Irons et al, 2014) show that caricaturing tends to be effective particularly when performance is initially impaired, at least as long as accuracy does not become so poor it hits floor.…”
Section: Caricaturing and Difficulty Of The Expression Recognition Tasksupporting
confidence: 64%
“…In a previous study, we have shown that caricaturing improves AMD patients' ability to perceive facial identity-that is, how one person's face differs from another's-across a wide range of vision loss severities, including for patients with mild, moderate, and even severe vision loss (legally blind; Lane, Rohan, Sabeti, Essex, Maddess, Barnes, et al, 2018). The identity caricaturing benefits in AMD patients also paralleled those in a partial simulation of AMD that used normal vision observers shown face images with added blur (Dawel et al, 2019;Irons et al, 2014;McKone, Robbins, He, & Barnes, 2018).…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…We thus also asked about image enhancement , which has the potential to improve perception of all aspects of faces. We explained that, in image enhancement, patients would view faces on computers, tablets, or smart glasses [41,42] with the faces digitally altered in ways that have been reported to improve low-resolution face perception (e.g., making the face larger [15,43]; increasing the contrast of medium and high spatial frequencies [44,45]; or caricaturing the face, i.e., exaggerating its appearance away from the average to make identification easier [4648]). Participants were on the whole very positive about trying image enhancement technology if and when it became available, particularly on TV and/or computer screens (90% support; e.g., one patient mentioned this would be useful when skyping his family), and via smart glasses (90% support).…”
Section: Resultsmentioning
confidence: 99%
“…Famous faces have been used in studies of processing differences for familiar versus unfamiliar faces (Johnston & Edmonds, 2009) or familiar faces varying in social importance to self (famous faces vs. friends' faces, Keyes & Zalicks, 2016). Famous faces can also been used for linking face recognition ability to personality traits such as extraversion (Lander & Poyarekar, 2015), understanding perceptual face coding via image manipulations (e.g., caricaturing, Lee, Byatt, & Rhodes, 2000; Itz, Schweinberger, & Kaufmann, 2016), investigating manipulations to improve poor face recognition (e.g., in the bionic eye, Irons et al, 2017; or for other‐race faces, Dawel et al, 2019), dissociating physical face versus identity representations in the brain (Rotshtein, Henson, Treves, Driver, & Dolan, 2005), and investigating associative memory in parahippocampal cortex (Bar, Aminoff, & Ishai, 2008). Also of relevance in young adults, famous face tests can be used as part of general neuropsychological evaluation (e.g., for amnesia following brain injury, Rizzo, Venneri, & Papagno, 2002), and are required for diagnosing prosopagnosia, both acquired and developmental (e.g., in Australia the MACCS Famous Face Test 2008, Supp to Palermo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%